EFEKTIVITAS SUPERVISI KUNJUNGAN KELAS OLEH KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA GURU - Erita Erita (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by still many obstacles faced by teachers, including, not all teachers develop syllabus and plan for implementing learning  properly. In addition, the researchers also found that some teachers did not make plans for implementing learning in carrying out classroom learning, so the teacher taught without preparation at all. Then in the implementation of teaching and learning interactions, not all teachers use teaching aids and various learning models. The method used is less varied, only lectures and questions and answers. The purpose of this study was to improve teacher performance through supervision of class visits by principals. this research was conducted at SDN 26 Bathin Solapan. The subjects of this study were all six class teachers. This study uses school action research which consists of two cycles, with important stages such as planning, implementation, practice, and reflection. The results of the study prove that, there was an increase in assessment after supervision of class visits. The increase is as follows: in the first cycle the class I teacher got an average score of 71 while in the second cycle it increased to 86.3. Class II teacher, in the first cycle got an average score of 69.6, while the second cycle increased to 86.6. Class III teachers in the first cycle got an average score of 68.3, while the second cycle increased to 83.6. Grade IV teachers in the first cycle got an average score of 67, while the second cycle increased to 89. The fifth grade teacher in the first cycle got an average score of 69.6, while the second cycle increased to 87.3, and the class VI teacher in the first cycle got the average score. 72, while the second cycle increased to 89. From these results, researchers can conclude that by implementing supervision of class visits by principals can improve teacher performance at SDN 26 Bathin Solapan